2017
DOI: 10.17509/jpki.v3i1.7476
|View full text |Cite
|
Sign up to set email alerts
|

Lost to Follow-Up : Reasons and True Outcome for Patients on Arv Treatment in Teratai Clinic Bandung Indonesia

Abstract: Klinik RSHS Teratai HIV telah merawat pasien dari September 2004 sampai Desember 2009, sebanyak 2.060 ODHA dan 1290 menerima ARV (63%). Selama periode ini, sebesar 11% (141 orang) kehilangan kontak lebih tinggi dari keseluruhan persentase di Indonesia yaitu 10,7% (Depkes, 2009). Tujuan dari penelitian ini adalah untuk menyelidiki hasil yang benar dan faktor hilang tindak lanjut ARV di klinik RSHS Teratai ARV. Penelitian ini menggunakan metode wawancara mendalam dengan 25 pasien HIV / AIDS bawah pengobatan ARV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
5
0
1
Order By: Relevance
“…Furthermore, they include unfamiliarity with health facilities, disconnection in communication with healthcare providers, and lack of understanding regarding women's needs. These barriers were more apparent for sub-risk group population such as homosexual, transgender, and PLWH with disabilities (Haroen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they include unfamiliarity with health facilities, disconnection in communication with healthcare providers, and lack of understanding regarding women's needs. These barriers were more apparent for sub-risk group population such as homosexual, transgender, and PLWH with disabilities (Haroen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Access to affordable healthcare service is also a concern among PLWH since their health is susceptible due to the virus progression in their body. The remaining significant number of PLWH was loss to follow-up (Handayani et al, 2017;Haroen et al, 2017;Widyanthini et al, 2014), and lower percentage of virally suppression (Januraga et al, 2018) was due to barrier to access healthcare services. Also, Previous study reported some inhibiting factors for PLWH in accessing healthcare services, which include stigma, long distances, lack of confidentiality, financial constraints, multiple appointments (Ayon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there seem to be advantages in scaling up ART at the community level as this may potentially increase early detection and reduce the burden in hospital clinics [ 46 ]. Also, the shorter waiting and travel time to the clinic may lead to lower patient’s costs and better uptake and adherence of ART [ 46 49 ]. In this scenario, the hospital and community health centres will have different roles (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transportation comprises the highest proportion of costs: 62 and 43 % for patients with CD4 cell counts below and above 200 cells/mm 3 , respectively, and this is comparable with the finding of Riyarto et al [ 16 ] in Indonesia. A study by Haroen et al [ 49 ] in Bandung, Indonesia, and international studies by Portelli et al [ 47 ], Brinkhof et al [ 48 ], and Posse et al [ 15 ] have shown that transportation costs are a common reason why patients cease ARV. This information provides another reason to scale up ART at community level, as it likely reduces transportation costs for patients and may increase the uptake of ART, especially of patients with CD4 cell counts <200 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 99%